Ventriculoperitoneal shunt disconnection associated with spontaneous knot formation in the peritoneal catheter. (22nd May 2013) - Lo, William B; Ramirez, Roberto; Rodrigues, Desiderio; Solanki, Guirish A
Abstract : A 10-year-old girl underwent distal ventriculoperitoneal (VP) shunt revision 3 weeks earlier and developed further shunt malfunction. During the current shunt revision, a disconnection at the straight connector site in the cervical subcutaneous tissue was confirmed and a knot was identified in the peritoneal catheter. Postoperatively, the patient made a rapid neurological recovery and was discharged 48 h later. This is the first case of VP shunt disconnection associated with a spontaneous distal knot formation. The likely mechanism was that the spontaneously formed knot acted as an anchor at the peritoneal wall, preventing free relative movement of the distal catheter. The resultant tension led to failure at the weakest point of the system, resulting in a disconnection at the proximal straight connector site.